Who Is to Blame? Official Discourse and Ethnic Diversity Attitudes During the 2011 Riots in England. Issue 5 (2nd February 2016) - Fasel, Nicole; Sarrasin, Oriane; Green, Eva G. T.; Mayor, Eric
Abstract : In 2011, the killing of a Black man by a police officer triggered violent riots across England. In a context where ethnic minorities are rarely openly blamed, we examined the lens through which the events were interpreted in the official discourses of the British Prime Minister. A thematic content analysis (Study 1) revealed that, without explicitly blaming ethnic minorities, the discourses built on antagonistic normative references opposing a virtuous majority to threatening minorities. Then, based on online survey data of self‐declared Londoners (N = 223) during the riots, we analyzed (Study 2) how agreement with the discourses related to individuals' ethnocentrism and their understanding of the causes underlying the events. Results of regression analyses showed how agreement with the discourses related to blaming ethnic diversity for the riots and to higher ethnocentrism, especially among individuals least likely to discriminate against minorities (i.e., low in social dominance orientation). Agreement with the discourses was also linked to reduced blame of authorities. To conclude, we discuss the mobilization potential of political discourses on ingroup virtue and outgroup threat.